Analysis Ability Numeracy on Sundanese Manda Game in Mathematics Learning for Grade V in Elementary School - Hidayati, Femi; Ngazizah, Nur; Anjarini, Titi (Graduate Program Magister Manajemen Pendidikan, 2025)
The numeracy ability of fifth grade students of SDN Kedungpucang through the traditional Sundanese Manda game was examined in this study. The results of the AKM pre-test showed that the average student numeracy score was 50.33, below the school's KKM of 70. This study aims to analyze ability numeracy in games Sundanese manda in mathematics learning. This type of research is included in the qualitative descriptive category. with stages like data collection, data reduction, extraction conclusions, and verification. Tools for collecting data include observation , interviews , documentation , and sheets. Work student. Data analysis methods applied use approach analysis descriptive qualitative. Student performance was measured through active discussion, accuracy in solving problems, and application of mathematical concepts in real situations. The results of the study after the intervention increased significantly, with the average post-test being 67.33 or an increase of 17 points. Students involved in the game showed understanding operation count on concept numeracy in a way deep and contextual. Thus, integration game traditional sunda manda proven effective in develop skills numeracy.